Early Antibiotics and Childhood Obesity: Do Future Risks Matter to Parents and Physicians?. (February 2019) - Lipstein, Ellen A.; Block, Jason P.; Dodds, Cassandra; Forrest, Christopher B.; Heerman, William J.; Law, J. Kiely; Lunsford, Douglas; Winkler, Paula; Finkelstein, Jonathan A.
To understand how parents and physicians make decisions regarding antibiotics and whether a potential associated risk of obesity would alter decisions, we conducted a qualitative study of parents and physicians who care for children. Parent focus groups and physician interviews used a guide focused on experience with antibiotics and perceptions of risks and benefits, including obesity. Content analysis was used to understand how a risk of obesity would influence antibiotic decisions. Most parents (n = 59) and physicians (n = 22) reported limited discussion about any risks at the time of antibiotic prescriptions. With an acute illness, most parents prioritized symptomatic improvement and chose to start antibiotics. Physicians' treatment preferences were varied. An obesity risk did not change most parents' or physicians' preferences. Given that parent-physician discussion at the time of acute illness is unlikely to change preferences, public health messaging may be a more successful approach to counter obesity and antibiotics overuse.